Analogiese Eksistensie(2). Aantekeninge by die etiek van J A Heyns - Van Wyk, J. H. (Verbum et ecclesia, 1995)
Analogical existence. Comments on the ethics of J A Heyns. In a previous article it has been argued that at the heart of Heyns's ethics lies the idea of analogical existence, which basically means that rnan must reflect God because he is created in the image of God. In that connection a few features of the ethics of Heyns were explained, a discussion which is being continued in this article.